PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN VIDEO PEMBELAJARAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Irawan; Mariyam; Citroresmi Prihatiningtyas, Nindy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) determine whether there is a difference in students' mathematical concept understanding ability between classes using the TGT cooperative learning model assisted by AI learning videos and those using direct learning. 2) determine how much influence the TGT learning model assisted by AI learning videos has on students' mathematical concept understanding ability. 3) determine how students' activities are when the TGT learning model assisted by AI learning videos is applied. The research used is a quasi-experimental research with a posttest-only control design. The population in the study were students of class VIII of SMP IT Al-Ayyuby. The sample used was saturated sampling. The data collection technique used a test technique in the form of mathematical concept understanding ability questions in the form of essays containing 5 questions. The data analysis technique used the Mann Whitney U-Test, Effect Size test. The results of the analysis showed that the data were normally distributed. The results of the study showed 1) differences in students' mathematical concept understanding abilities in the TGT learning model assisted by AI learning videos compared to conventional methods. After being calculated with a two-sample t-test with the results of t count> t table, namely 5.598> 2.015, Ha was accepted and Ho was rejected. 2) The TGT model assisted by AI learning videos had a high effect on students' mathematical concept understanding abilities, in the experimental class that received the TGT model treatment assisted by AI learning videos with the results of the effect size test of 1.55 high criteria. So it can be concluded that there is an influence of the TGT model assisted by AI learning videos on students' mathematical concept understanding abilities. 3) Student activities are classified as active when the TGT learning model assisted by AI learning videos is applied to students' mathematical concept understanding abilities with an activity percentage of 85%.